Leiomyoma with KAT6B-KANSL1 fusion: case report of a rapidly enlarging uterine mass in a postmenopausal woman - Alessandra J. Ainsworth; Nooshin K. Dashti; Taofic Mounajjed; Karen J. Fritchie; Jaime Davila; Rohini Mopuri; Rory A. Jackson; Kevin C. Halling; Jamie N. Bakkum-Gamez; J. Kenneth Schoolmeester (BMC, 2019)
Abstract Background Uterine leiomyomas, in contrast to sarcomas, tend to cease growth following menopause. In the setting of a rapidly enlarging uterine mass in a postmenopausal patient, clinical distinction of uterine leiomyoma from sarcoma is difficult and requires pathologic examination. Case presentation A 74-year-old woman presented with postmenopausal bleeding and acute blood loss requiring transfusion. She was found to have a rapidly enlarging uterine mass clinically suspicious for sarcoma. An abdominal hysterectomy and bilateral salpingo-oophorectomy were performed. A 15.5 cm partially necrotic intramural mass was identified in the uterine corpus. The tumor was classified as a cellular leiomyoma. RNA sequencing identified a KAT6B-KANSL1 fusion that was confirmed by RT-PCR and Sanger sequencing. After 6 months of follow-up, the patient remains asymptomatic without evidence of disease. Conclusion Prior studies of uterine leiomyomas have identified KAT6B (previously MORF) rearrangements in uterine leiomyomas, but this case is the first to identify a KAT6B-KANSL1 gene fusion in a uterine leiomyoma. While alterations of MED12 and HMGA2 are most common in uterine leiomyomas, a range of other genetic pathways have been described. Our case contributes to the evolving molecular landscape of uterine leiomyomas.